Ethnic origins of the peoples of northeastern Asia - Levin, M. G. (Maksim Grigorʹevich), 1904-1963 (Anthropology of the North: translations from Russian sources, 1963)
This is a translation from a Russian work published in 1958, one of the major works of a well-known and prolific writer. It deals with the origins of the small nations and peoples of central Siberia and northeastern Asia. Many guesses have been made about these peoples but most have not been substantiated, because of the lack of field work or because the materials on them had not been analysed and published. Levin has reviewed the old materials, gathered and analysed hitherto unpublished ones, and personally surveyed many of the peoples as a member of the Russian Northeastern Expedition. He makes use of all the data of physical anthropology, ethnography, archaeology, and linguistics on the peoples he describes and has thus provided a definitive work on a nearly forgotten segment of mankind inhabiting an extensive territory.